MARIA DA PENHA LAW IN COMBATING DOMESTIC VIOLENCE: ADVANCES AND CHALLENGES (REMUNOM, 2024)
The tackling of domestic and family violence against women in Brazil has gained prominence since the enactment of the Maria da Penha Law, legislation aimed at protecting and ensuring the rights of women who are victims of violence. This study aims to analyze the contributions and challenges of the Maria da Penha Law in combating domestic and family violence against women. The specific objectives are to identify the advancements provided by the law, examine the difficulties in its implementation, and suggest measures to enhance the effectiveness of the legislation. The research seeks to answer the following question: what are the main contributions and challenges of the Maria da Penha Law in addressing domestic and family violence against women? The methodology adopted is bibliographical, based on a literature review on the subject. The results indicate that the Maria da Penha Law has brought significant advances in women's protection and awareness of gender violence, but it still faces challenges such as lack of resources, the need for better training of involved professionals, and cultural resistance. It is concluded that, despite the progress made, it is essential to continue improving the implementation strategies of the law to ensure its full effectiveness.